(3eMGVQGJ aj GdEbJUGO GdLRFj (B01 : s (3JMdjd fXQj h JWHjbj (B/ s - (3Tfha, Mcjes; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2020)
(3Yde GdGbJUGO h GdeTcdI GdGbJUGOjI h fXQjI GdWdH h fXQjI GdYQV h JhGRf GdShb h GdeQhfGJ h JWHjbGJ Ydi JhGRf GdShb h GdJWQb Gdi fXQjI Sdhc GdeSJgdc (B( (3GdefaYI GdbjGSjI (B) (3h cPG (B( (3efMfjGJ GdShGA(B) .s
(3eQGLY U(B.155s
Keywords: (3GdGbJUGO GdLRFjs